A STUDY ON DYNAMIC SEPARATION OF SILICA SLURRY USING A ROTATING MEMBRANE-FILTER .1. EXPERIMENTS AND FILTRATE FLUXES - PARK, JY; CHOI, CK; KIM, JJ (ELSEVIER SCIENCE BV, 1994)
The microfiltration performance of an axially rotating filter was investigated experimentally with an aqueous slurry containing fine silica particles. The effects of the rotating speed of the inner filter, gap size, feed concentration and feed rate on the filtrate flux were examined. Since Taylor vortices generated in its annular gap reduce the cake formation on the surface of the inner filter medium, an efficient removal of water from the slurry was achieved to a certain degree. The results show that continuous filtration is possible in turbulent Taylor-vortex regimes. By dividing the experimental data into two groups, transient and pseudosteady, empirical correlations for the dimensionless filtrate flux were obtained in terms of the Taylor number and the ratio of the annular gap to the inner cylinder radius, respectively.